News Notes. - Griffin, Charles H. (The Accounting Review, 1967)
Abstract The article presents information on the joining of accounting professors in various universities and colleges in the U.S. The following joined the faculty of the department of accounting at the University of Florida in September 1966: Kemper W. Merriam, as professor, Felino J. Valiente, associate professor, Eugene McCormick, assistant professor. R. J. West has been promoted to associate professor. Thomas Humble is teaching at the University of Pusan, Korea, during the fall semester. Charles Mecimore joined the faculty at the University of Georgia after spending the summer with Ernst & Ernst in Birmingharn, Alabama. Don H. Taylor joined the faculty of Georgia State College in June and Fred A. Thornton in September, both at the rank of assistant professor. John W. Creighton has been named chairman of department of Naval Postgraduate School to replace James M. Fremgen upon his accepting a visiting professorship at the University of Hawaii for 1967-68. H. Arthur Hoverland has been elected chairman of the college of management psychology of TIMS.